Assessing the accuracy of commercially available gas sensors for the measurement of ambient ozone and nitrogen dioxide. Issue 11 (2nd November 2018) - Isiugo, Kelechi; Newman, Nicholas; Jandarov, Roman; Grinshpun, Sergey A.; Reponen, Tiina
Abstract: The objective of the National Institute for Occupational Safety and Health (NIOSH) accuracy criterion is to ensure that measurements from monitoring devices are within ±25% of the true concentration of the analyte with 95% certainty. To determine whether NO2 and O3 sensors meet this criterion, three commercially available units (Cairclip O3 /NO2, Aeroqual NO2, and Aeroqual O3 sensors) were co-located three times with validated instruments (NOx chemiluminescence [NO2mon ] and photometric O3 analyzers [O3mon ]) at an outdoor monitoring station. As cofactors of sensor performance such as temperature (T) and relative humidity (RH) potentially influence the response of NO2 and O3 sensors, corrections for cofactors were made by using T, RH, and the sensor measurements to predict measurements made by NO2mon and O3mon during the first co-location period (training dataset). The developed models were tested in the merged data obtained from the second and third co-location periods (testing dataset). In the training and testing datasets, the mean NO2 as measured by NO2mon was 4.6 ppb (range = 0.4–35 ppb) and 9.4 ppb (range = 1–37 ppb), respectively. The mean O3 in the training and testing datasets as measured by O3mon was 38.8 ppb (range = 1–65 ppb) and 35.7 ppb (range = 1–61 ppb), respectively. None of the sensor measurements in the training dataset were within the NIOSH accuracy criterion (mean error ≥25%). After correcting for cofactors of sensor performance, the accuracy of the Cairclip O3 /NO2 and the Aeroqual O3 sensors considerably improved when tested with the testing dataset (mean error = -1% and 14%, respectively). However, the Aeroqual NO2 sensor had an error that was not within ±25%. Raw measurements from the tested sensors may be unsuitable for assessing workers' exposure to NO2 and O3 . Corrections for cofactors of Cairclip O3 /NO2 and Aeroqual O3 sensor performance are required for more accurate occupational exposure assessment.